Komodifikasi Ekonomi Politik Media pada Kanal Youtube - Yehezkiel, Niko; Rusadi, Udi (As-Syirkah: Islamic Economic & Financial Journal, 2024)
The presence of the YouTube platform actually makes it easier for the commodification of political communication to occur. Unfortunately, the impact of commodification is not only positive but also has a negative influence. Negative influences include the loss of family values that have long been embedded in society. while the positive impact is the potential to increase people's income. The question is how commodification of political communication occurs on the YouTube platform and to what extent does YouTube have an impact on the commodification of political communication? This article is intended to analyze the commodification process on YouTube channels, both in terms of content, audiences and workers. The basic theory used is Vincent Mosco's commodification theory. The author uses qualitative methods, not to conclude, but only to provide an illustration. Data was obtained through literature study with online searches. The analysis will answer the question, first, how the commodification of political communication occurs on the YouTube platform. Second, the extent to which YouTube has a positive and negative impact on the commodification of political communication. As a reflection, the success of commodification will depend on the positive impact it has. If the use of YouTube can be optimized, it will have implications for the progress of communication.